Bond strength of glass fiber posts submitted to different luting protocols - De Landa, Fabiano Vieira; Miranda, Jean Soares; De Carvalho, Rodrigo Furtado; Kimpara, Estevão Tomomitsu [UNESP]; Leite, Fabíola Pessôa Pereira (EDIPUCRS, 2016)
Objective: evaluate the effect of different luting protocols on the bond strength of glass fiber posts. Methods: Forty human canine teeth were randomly divided into four groups: Relyx U100/Endofill (R+E), Panavia F2.0/EndoFill (P+E), Relyx U100/Sealer 26 (R+S), Panavia F2.0/Sealer 26 (P+S). After the luting procedures, the samples were subjected to thermocycling (6.000 cycles; at 5±1 °C and 55±1 °C) and then sectioned in a precision cutting machine (Isomet 1000 Precision Saw) into 4 cuts of 2mm regarding to different deepness: Apical, Medium Apical, Medium Coronal, and Coronal. Next, the cuts were submitted to push-out test in a universal testing machine (EMIC) with load cell of 50N, at crosshead speed of 0.5mm/min. Results: They were obtained according to the different luting deepness (p?0.05) (MPa): 1) apical-R+E (1.35±1.28), P+E (2.70±0.89), R+S (3.89±0.70), P+S (4.30±1.02); 2) medium apical-R+E (1.38±1.28), P+E (2.98±1.43), R+S (4.02±1.14), P+S (4.49±1.82); 3) medium coronal-R+E (2.46±0.73), P+E (3.72±0.78), R+S (4.85±0.71), P+S (6.14±0.73); 4) coronal R+E (5.59±1.08), P+E (5.74±1.06), R+S (6.71±1.07), P+S (7.40±1.51). Conclusion: There was a relationship between the luting protocol of the glass fiber post and the endodontic cement. Eugenol plays an important role inside the dentinal tubules by interfering negatively in the bond strength to root dentin.
Keywords: Adhesion; Endodontic cement; Glass fiber post